EFEKTIVITAS EDUKASI SIGAP BALITA MENGGUNAKAN MEDIA POSTER DAN LEAFLET TERHADAP PENINGKATAN PENGETAHUAN ORANG TUA DALAM PENGENDALIAN GIZI LEBIH BALITA DI KELURAHAN RAGUNAN, JAKARTA SELATAN TAHUN 2025 - Vivi Silawati; Syafira Bayu Putri; Beby Alya Rahman Nasution; Angina Fajri Damayanti; Shabrina Azka; Mulhayail Dayyani Diah Abdullah; Bella Dian Syah Fitri (PT. Hasba Edukasi Mandiri, 2026)
Introduction: Overweight in toddlers is a nutritional problem commonly found in urban areas and can affect children's health and growth and development. This condition increases the risk of obesity and non-communicable diseases in later life if not addressed early on. Community midwifery care through promotional and preventive activities, particularly health education using leaflets and posters, plays an important role in increasing parents' knowledge about controlling overweight in toddlers. Method: One group pre-test post-test approach. The sample consisted of 10 toddlers. Sampling techniques included interviews, observations, anthropometric examinations, and recording on the Health Card (KMS). The intervention was health education on overnutrition through the SIGAP BALITA program using posters and leaflets. Results: Statistical tests showed a p-value < 0.001, indicating a significant effect. Conclusion: Providing education using posters and leaflets had a significant effect on increasing parents' knowledge in controlling overweight in toddlers.